Short-term electric quantity load accurate prediction method - WANG PING; LIANG LING; HUANG YUSONG; XIA TIAN; SHI SHI; MA JIANWEI; CHEN SHENG; LIU XIAOFANG; ZHOU ZHONGQIANG; ZHANG HONGLUE (2020)
The invention relates to the field of electric power engineering, in particular to a short-term electric quantity load accurate prediction method, which comprises the steps of collecting electric quantity, load data, historical meteorological information and holiday data; cleaning data exception or data missing by adopting a replacement method and a difference method, and cleaning data asynchronization by adopting an average value method and a forced synchronization method; acquiring cleaned temperature and electric quantity load data, calculating to obtain an average electric quantity load under each temperature gear, drawing a temperature and electric quantity load influence curve, and taking a temperature interval with gentle electric quantity load trend as a reference electric quantityload temperature interval; classifying the electric quantity load in each temperature interval and calculating an average value, and considering a time-sharing characteristic for a load model to obtain an electric quantity t